ANALISIS PENGARUH KERAGAMAN PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP MINAT BELI ULANG MELALUI BRAND IMAGE PADA KONSUMEN ROCKET CHICKEN - Henny Welsa; Ignatius Soni Kurniawan; Risang Nagar (Journal Competency of Business, 2021)
This study aims to determine the effect of product diversity, price perception, and location on repurchase intention through the intervening variable brand image on Rocket Chicken customers. The population in the study were 100 Rocket Chicken buyers. The sampling technique in this study was an online questionnaire via Google Forms which was distributed randomly to Rocket Chicken customers. The results show that product diversity and price perception have a significant effect on brand image with each significance value of 0.000 and 0.017 which is smaller than 0.05, then for locations that have a significant value above 0.05, namely 0.316, it does not have a significant effect. to brand image. Significant values of brand image and location on repurchase intention are 0.000 and 0.002 where a significant value below 0.05 means that these two variables have a positive influence on repurchase intention, while product diversity and price perception have a significant value on repurchase requests. are 0.098 and 0.245 have no significant effect on repurchase interest